Possibilities of documentation management during bladder catheterization - Krocová, Jitka; Prokešová, Radka (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2020)
Together, careful record keeping on bladder catheterization and accepting the indication of bladder catheterization form one area of preventing catheter-associated urinary tract infection – CAUTI. Regarding the prevention of these infections, not only one preventive factor is applied, but sets of measures are preferred. The goal of this review study was to determine what methods of catheterization records are used and what are the possibilities of these records. Furthermore, the study provides an overview of indications for catheterization that are accepted in clinical practice. Studies show the effectiveness of the implementation of the so- called nurse-led protocol when nurses regularly re-evaluate the reasons for catheterization. Part of the protocol is an overview of indications for catheterization that are accepted at the workplace. Regarding the prevention of healthcare-related urinary tract infections, the effectiveness of multifactorial prevention measures has been clearly proven. Therefore, we followed the list of measures that were implemented together with a record of catheterization and the indication for bladder catheterization. The included articles were searched in full-text databases that were focused on healthcare – ProQuest STM + Hospital Collection – Medline, Web of Science, and citation databases – PubMed, Scopus, Google Scholar. The full texts of the articles were retrieved after studying the abstracts, and assessed as relevant or potentially relevant sources. The studies were selected using keywords: urinary tract infection, indication, bladder catheterization, prevention, documentation, and according to other criteria – full text article, peer-reviewed periodicals, English language, and a period of publication between 2011 and 2018. The result included 13 studies.
Keywords: Bladder catheterization; Documentation; Indication; Prevention; Urinary tract infection